2005
DOI: 10.1002/ffj.1460
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of the oil ofCleome iberica DC.

Abstract: The essential oil was isolated by steam distillation from the aerial parts of Cleome iberica DC. at a yield of 0.1% w/w, based on dry weight. The oil was analysed by a combination of GC and GC-MS; 26 components were identified, constituting 99.8% of the oil. The main constituents of the essential oil were carotol (21.8%), germacrene D (15.8%), β β β β β-cubebene (15.5%), trans-nerolidol (5.6%), δ δ δ δ δ-cadinene (4.5%) and hexyl acetate (4.0%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
0
3
1
Order By: Relevance
“…[27] and C. iberica DC. [28] However, the present study revealed that C. droserifolia is very rich in this compound compared to these plants. Nerolidol is used to enhance flavor and aroma and has been used as a topical skin penetration enhancer, therefore integrated into the manufacturing of cosmetic and non-cosmetic products.…”
Section: Essential Oil Compositioncontrasting
confidence: 55%
“…[27] and C. iberica DC. [28] However, the present study revealed that C. droserifolia is very rich in this compound compared to these plants. Nerolidol is used to enhance flavor and aroma and has been used as a topical skin penetration enhancer, therefore integrated into the manufacturing of cosmetic and non-cosmetic products.…”
Section: Essential Oil Compositioncontrasting
confidence: 55%
“…In addition, the high sesquiterpene concentration identified in the GLS oil sample was akin to the Egyptian C. chrysantha seed and herb oil samples [10]. Importantly, α-copaene was also one of the few constituents previously identified in other Cleome species [8,10]. Most of the other components from C. spinosa essential oils are being reported for the first time for the genus.…”
mentioning
confidence: 66%
“…Although several species of Cleome have been noted for their uses in folk medicine, only few chemical studies of their essential oils have been published [8,[9][10][11][12]. A literature survey revealed that the essential oils of C. spinosa have not been the subject of previous study.…”
mentioning
confidence: 99%
“…β-cubebene has a pleasant aroma translated as fruity and citrus. This compound is commonly found in the essential oils of several species [ 40 , 41 ] with the third most abundant member of the essential oil being obtained from cinnamon leaves ( Cinnamomum osmophloeum ) [ 42 ].…”
Section: Resultsmentioning
confidence: 99%